Contributions of postcolonialism to the cultural curriculum of Physical Education - Júnior, Flávio Nunes dos Santos (2019)
Hurried perceptions claim that the problems of colonialism have been dissolved, ended, and that now we live in a free time of any conflict or tension. Postcolonial thinking beckons the opposite. There is a clear recognition that forces of domination have only been resignified, marking the passage from one historical configuration or conjuncture of power to another, thus problems of dependence, underdevelopment and marginalization, very characteristic situations of the colonial period, persist vigorously in the post- coloniality. In an effort to decolonize the Physical Education curriculum, a group of teachers was inspired by postcolonial arguments and developed pedagogical experiences in public elementary schools. The documents that the teachers produced as a way of recording the pedagogical practice were submitted to the confrontation with the postcolonial referential of Homi Bhabha and the cultural perspective of Physical Education. The results show a political-pedagogical practice in favor of those who suffered, and still suffer, with the “heavy hand” of colonial imperial power.